Hubungan Persepsi Siswa-Siswi Sekolah Dasar Terhadap Perilaku Kekerasan Oleh Orang Tua Di Kota Jambi - Iis Hartini; Suandi Suandi; Fuad Muchlis (Mahesa Research Center, 2020)
In Jambi Province, the behavior of violence against children was quite high, reaching 72 children each year. This study is conducted at SDN 47, SDN 69, and SDN 208 Jambi City with a population of 6th grade students with a sample of 90 people. The variables studied consists the types of violence experienced by children, children's perceptions of violence and socio-economic factors that influence the occurrence of violence against children. The aspects of violence against children studied were physical violence, psychological violence, and sexual violence. The aspects of perception are consists of cognition, affection and conation. This research was conducted using descriptive analytical method, in quantitative analysis carried out by descriptive statistical analysis and inferential statistics using chi square correlation with categorical data types. The results of this study concluded that psychological violence (22%) was mostly experienced by these students. Aspect of children's perceptions of violence can be concluded that these students understand about violence against children and do not agree with violence against children. The socio-economic variables that have a significant relationship with violent behavior are maternal education (0,027) and maternal age (0,041) where the probability value shows a value less than 0.05. It means that maternal education and maternal age are related to violent behavior in children.